2021
DOI: 10.15408/sjie.v10i1.18752
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Economic Growth: Empirical Study of 10 Asia-Pacific Countries

Abstract: The purpose of this research to examine influence several independent variables, especially corruption, foreign direct investment (FDI), population growth, and government expenditure on the economic growth of 10 Asia-Pacific countries, and prove the hypothesis of the sand wheels theory whether corruption causes a decline and a slowdown in economic growth. This study uses panel data. The results showed that the variables of corruption have a negative impact on economic growth, foreign direct investment (FDI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
2
0
1
1
Order By: Relevance
“…In addition, FDI can help boost exports by expanding the capacity and competitiveness of domestic production. This result is consistent with the findings of multiple studies (Mehic et al, 2013;Alvarado et al, 2017;Hayat, 2017;Sultanuzzaman et al, 2018;Dinh et al, 2019; http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v12i1.29975 Shittu et al, 2020;Zeeshan et al, 2020;Mohamed et al, 2021;Nasir et al, 2021;Orji et al, 2021;Ahmad et al, 2022), which have found that an increase in FDI inflows can stimulate economic growth. In addition, Raza et al (2021) discovered that countries with high institutional quality tend to have stronger economic growth and more foreign direct investment (FDI) inflows.…”
Section: Resultssupporting
confidence: 91%
“…In addition, FDI can help boost exports by expanding the capacity and competitiveness of domestic production. This result is consistent with the findings of multiple studies (Mehic et al, 2013;Alvarado et al, 2017;Hayat, 2017;Sultanuzzaman et al, 2018;Dinh et al, 2019; http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v12i1.29975 Shittu et al, 2020;Zeeshan et al, 2020;Mohamed et al, 2021;Nasir et al, 2021;Orji et al, 2021;Ahmad et al, 2022), which have found that an increase in FDI inflows can stimulate economic growth. In addition, Raza et al (2021) discovered that countries with high institutional quality tend to have stronger economic growth and more foreign direct investment (FDI) inflows.…”
Section: Resultssupporting
confidence: 91%
“…Based on Adam Smith's classic theory that natural resources, human resources, and capital are the three determinants of economic growth. Foreign direct investment and government expenditure positively and significantly affect economic growth (Nasir et al, 2021). However, this study shows the opposite result, where Foreign direct investment and government spending have a negative and significant effect on economic growth.…”
Section: Resultscontrasting
confidence: 65%
“…The R-Squared value is 0.96 which means that the independent variable studied can explain 96% of the variation in the dependent variable change, while the remaining coefficient of 0.04 or 4 % is another variable outside the model that can explain changes in the dependent variable.Bali's Economy Growth will rise more than 1 %. The results of this study are in line with research conducted byTriharjanto et al, (2022), andWibowo et al, (2021) regarding the development of Bali's Economy GrowthCONCLUSIONBali as a province with economic potential should have gained demography bonuses earlier and with longer duration than any other region or national scale. But, there are certain conditions and terms to make it happen.…”
supporting
confidence: 89%